PENGAMBILAN KEPUTUSAN KONSUMEN MILENIAL DI SURABAYA DALAM MEMBELI PRODUK HALAL MELALUI APLIKASI ONLINE - Atmajawati, Yayah; Agustin, Sasi; Tegowati, Tegowati (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This research aims to analyze the influence of price perceptions, halal product trust, after-sales service and online promotions on online purchasing decisions. Methode: This research is quantitative. The sample consisted of 50 respondents who had purchased halal products via online applications. The sampling method used a purposive sampling technique: consumers in Surabaya who had purchased online. Data analysis used multiple linear regression with SPSS 20.0. Research Findings: The findings in this research are as follows: 1) Price perceptions do not affect online purchasing decisions; 2) After-sales service influences online purchasing decisions; 3) Online promotions influence online purchasing decisions; 4) Trust does not affect online purchasing decisions. Theoretical Contribution: Can provide additional information for readers and serve as a reference if they want to research further regarding the results obtained by this research. Practical Implications: This research is expected to be used to predict actual online consumer purchases through the variables studied. Research limitations: This research only examines the variables of price perception, after-sales service, halal product trust, online promotions, and online purchasing decisions. Meanwhile, the sample is only for consumers who have purchased halal products online.